SURXONDARYO VILOYATINING SHIMOLIY HUDUDLARIDA UCHROVCHI YONG‘OQ (JÚGLANS RÉGIA) O‘SIMLIGIDAGI NEMATODALARNING O‘RGANILISHIGA DOIR ADABIYOTLAR TAHLILI - Abdujalilova Maftuna Isakjonovna; Bobokeldiyeva Shaxnoza Abdusamad qizi; Jo’rayeva Samiya Hasanovna (Journal of new century innovations, 2024)
Annotation: A review of sources based on scientific literature on the study of nematodes found in the walnut plant in the northern regions of surkhandarya region, in particular, a brief analysis of scientific work conducted in foreign, cis countries and uzbekistan is presented.